The Relationship Of The Quality Of Administrative Services And Bpjs Patient Satisfaction In The Inpatient Room X Rumkit Tk Ii Dr. Soepraoen Kesdam V/Brawijaya Malang In Malang City - Sutarji; Ratna Wardani; Ardi Bastian; Panca Radono (Universitas STRADA Indonesia, 2023)
Quality of service is one of the factors that people consider when choosing a health facility to use. Service quality is a measure to measure patient satisfaction. The aim of the research is to analyze the relationship between the quality of administrative services and BPJS patient satisfaction at Rumkit Tk.II dr. Soepraoen Kesdam V/Brawijaya Malang City Malang City. This research uses a quantitative research design with a cross-sectional approach. The population is all patients or BPJS patient waiters in Inpatient Room X Rumkit Tk.II dr. Soepraoen Kesdam V/Brawijaya Malang City with a sample of 78 respondents using a purposive sampling technique. The independent variable is the quality of administrative services and the dependent variable is BPJS patient satisfaction. Data were collected using a questionnaire and analyzed by the Spearman Rho test with the help of SPSS. The research results showed that the majority of respondents (56.41%) were good (44 people). the majority (65.3%) of respondents were satisfied (51 people). The cross tabulation results showed that the majority expressed satisfaction and good quality, namely 28 people (54.9%). The Spearman's rho statistical test obtained a P-value of 0.000 < 0.05 and a Correlation Coefficient of 0.340, which means there is a relationship between the quality of administrative services and patient satisfaction. At TK II Hospital, dr. Soepraoen Kesdam V/Brawijaya Malang City. The better the quality of administrative services, the more patient satisfaction will increase, so it is hoped that hospital bureaucracy can improve the quality of administrative services for patient satisfaction.